Improved Compliance and Comprehension of a Surgical Safety Checklist With Customized Versus Standard Training: A Randomized Trial. Issue 3 (September 2018) - Rakoff, David; Akella, Krishna; Guruvegowda, Chandrashekar; Chhajwani, Sunil; Seshadri, SriKrishna; Sola, Srikanth
Abstract : Objective: This study aimed to determine the effect of customized training versus standard readily available training on surgical safety checklist (SSCL) compliance and comprehension. Background: The success of the SSCL in reducing surgical mortality and morbidity depends largely on the degree of compliance among health care workers with the checklist's components. We hypothesized that a customized training program would improve comprehension of the SSCL components among health care workers. Methods: We prospectively evaluated compliance and comprehension of a locally modified SSCL among surgeons, anesthesiologists, nurses, and perfusionists who were randomized to standard versus customized training in the department of cardiac and thoracic surgery. Standard training included videos, posters, and didactic sessions obtained from the World Health Organization. Customized training consisted of a department-specific orientation video (using local staff as actors), locally made posters, and didactic sessions. Comprehension was assessed by a written exam after each training program. Verbal and written compliance with the SSCL was measured within the operating theater by trained observers. Results: We observed a total of 244 surgeries for SSCL compliance. Comprehension of the didactic material provided in the training programs was higher in the customized versus the standard training group (75% versus 30%; P < 0.0001). Verbal compliance was higher in the customized versus standard training groups (87% versus 49%; P < 0.0001). Written compliance was 100% for both the customized and standard training groups. Conclusions: A customized training program improves verbal compliance and comprehension among health care workers when implementing an SSCL, compared with standard readily available training.